2003
DOI: 10.2139/ssrn.454500
|View full text |Cite
|
Sign up to set email alerts
|

Moral Hazard and Other-Regarding Preferences

Abstract: The paper aims at obtaining new theoretical insights into organizational behavior by combining the standard moral hazard models of principal-agent relationships with theories of other-regarding (social or interdependent) preferences, in particular, inequity aversion theory. In the benchmark model, the principal and the agent are both risk neutral, while the agent is wealth constrained and hence the basic tradeoff between incentives and rent extraction arises. I show that other-regarding preferences interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…Despite the general tendency of inequity aversion to generate wage compression, Itoh (2004), Rey-Biel (2008), and Bartling and von Siemens (2010) identify some conditions under which increased pay inequality can result. Specifically, if limited liability prevents the principal from punishing the agent by reducing her pay, he can instead punish her by paying another agent more.…”
Section: Reduced Wage Sensitivitymentioning
confidence: 99%
“…Despite the general tendency of inequity aversion to generate wage compression, Itoh (2004), Rey-Biel (2008), and Bartling and von Siemens (2010) identify some conditions under which increased pay inequality can result. Specifically, if limited liability prevents the principal from punishing the agent by reducing her pay, he can instead punish her by paying another agent more.…”
Section: Reduced Wage Sensitivitymentioning
confidence: 99%
“…For example, Stevens and Thevaranjan (2010) assert that the issue of moral hazard can be resolved in the principal-agent model if the agents are sensitised morally. 4 Likewise, Itoh (2004) proclaims that the presence of other-regarding preferences is of central concern in resolving the issue of moral hazard. We also have some other suggestions for minimising moral hazards like peer pressure in team work [Corgnet, et al (2015)]; the recommendation of deductible in insurance [Raaij (2016)]; prudential regulations in financial sector [Hellmann, et al (2000)] etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that other-regarding preferences may have a positive role in moral hazard situations [17][18][19]. The observation has stimulated research into a theoretical analysis of the contract theory.…”
Section: Introductionmentioning
confidence: 99%